Classic Drucker : - Drucker, Peter F. (Harvard Business Review Book, 2006)
For nearly half a century, Peter Drucker inspired and educated managers—and powerfully shaped the nature of business—with his landmark articles in Harvard Business Review. Here, framed by a thoughtful introduction from "HBR" editor Thomas A. Stewart, is a priceless collection of Drucker's most significant work. Through his unique lens, Drucker traces the evolution of the great shifts in organizations and the role of managers in the ongoing effort to balance change with continuity. He paints a clear, comprehensive picture of management thinking and practice—as it was and as it will be. Revealing a celebrated thinker at his best, Classic Drucker offers a wealth of insights and practical guidelines for managers seeking to address today's thorniest organizational challenges.For example, you'll find selections on how to enhance your company's innovative prowess, make effective decisions, raise knowledge workers' productivity, remain engaged and productive during a long work life, know when the assumptions on which your business was founded must change, and get the data you need to execute your company's competitive strategy. Doing what's right for your company will always be challenging. But thanks to the clear focus, broad vision, and practical wisdom of Peter Drucker, the task is now a little less daunting.